Measuring the concentration of some hormones in patients sera of polycystic ovaries (Baghdad Science Journal, 2025)
Extensive evaluation of 76 women with polycystic ovary syndrome compared with 25 fertile women as control group was achieved by routine investigations and hormonal study of each female which were done in one period during the menstrual cycle. Then the women with PCOS have been divided into 2 groups according to their menstrual cycle (irregular menstrual cycle) during assessing their hormonal profiles as follow:-1- (54) Patients with oligomenorrhea.2- (22) Patients with menorrhea. This study shows that the women with PCOs have different clinical features taken from a history of disease of all of the women.Those features were distributed as follow: 57.92% of them suffer from hirsutism. 19.24% suffer from irregular menstrual cycle, obesity in 67%, 9 patient with acne vulgaris, and more than 50% of them have most of the clinical symptoms at same time. It is also found that the hormonal disorder is the main cause of this disease with other cawes.